2017
DOI: 10.17925/ee.2017.13.02.81
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of Continuous Glucose Monitoring for People with Type 1 Diabetes and Impaired Awareness of Hypoglycaemia within North West London Clinical Commissioning Groups in England

Abstract: To assess the economic impact of providing real time continuous glucose monitoring (CGM) for people with type 1 diabetes (T1D) and impaired awareness of hypoglycaemia (IAH) within North West (NW) London clinical commissioning groups (CCGs). Methods: The eligible population for CGM and inputs for the economic budget impact model developed were derived from published data. The model includes cost of CGM; cost savings associated with lower hypoglycaemia related hospital admissions, accidents and emergency visits;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Flash glucose monitoring was reported to provide $474 AUD ($333 USD) cost savings over 1 year compared to SMBG and heterogeneous insulin delivery methods in the UK [28], based on the 'Novel Glucose-Sensing Technology and Hypoglycemia in Type 1 Diabetes: a Multicentre, Non-masked, Randomised Controlled Trial' (IMPACT study) [29]. A budget impact analysis in the UK reported CGM to have 'minimal budget impact' compared to SMBG when insulin delivery modality was either CSII or MDI [30]. The real option analysis approach with cash flow simulation of a cohort in Finland reported that integrated CSII and CGM systems provide $1,000,792 AUD ($704,029 USD) cost savings in comparison to MDI with SMBG over a lifetime [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flash glucose monitoring was reported to provide $474 AUD ($333 USD) cost savings over 1 year compared to SMBG and heterogeneous insulin delivery methods in the UK [28], based on the 'Novel Glucose-Sensing Technology and Hypoglycemia in Type 1 Diabetes: a Multicentre, Non-masked, Randomised Controlled Trial' (IMPACT study) [29]. A budget impact analysis in the UK reported CGM to have 'minimal budget impact' compared to SMBG when insulin delivery modality was either CSII or MDI [30]. The real option analysis approach with cash flow simulation of a cohort in Finland reported that integrated CSII and CGM systems provide $1,000,792 AUD ($704,029 USD) cost savings in comparison to MDI with SMBG over a lifetime [25].…”
Section: Resultsmentioning
confidence: 99%
“…Herman et al utilised CSII and MDI treatment effects based on the intensive and conventional treatment arms of the landmark diabetes control and complications trial (DCCT) published in 1995 which may not reflect contemporary management strategies or HbA1c treatment effects [24,57]. Economic evaluations that compared CGM to SMBG modelled treatment effects for HbA1c as a reduction of 0.23% (2.5 mmol/mol) to 0.6% (6.6 mmol/mol) [30,33]. Three studies that reported CGM was not cost-effective modelled a treatment effect for HbA1c less than 0.5% (5.5 mmol/mol) from the authors' own respective meta-analyses [14,17,33].…”
Section: Discussionmentioning
confidence: 99%
“…DM consists of a group of metabolic diseases that are characterised by hyperglycaemia due to a total, or relative, lack of insulin secretion and/or insulin resistance (Al-Maskari et al, 2011). The prevalence of type 1 DM is 187.7 per 100,000 (Chaugule et al, 2017) and type 2 DM is 5260 per 100,000 (Zghebi et al, 2017). Current classifications describe four sub-types of DM:…”
Section: Endocrinologymentioning
confidence: 99%
“…A cost-effectiveness analysis of data from the DIAMOND study showed that, in adults with T1D and elevated HbA1c (≥ 7.5%), CGM increased costs compared with SMBG but was a lifetime cost-effective intervention when clinical benefits (HbA1c reduction, daily strip use, and frequency of non-severe hypoglycemia) were taken into account [110]. Similarly, for high-risk patients with T1D and impaired hypoglycemia awareness, the economic impact of CGM is counteracted by lower hypoglycemia-related costs, reduced SMBG strip use, avoidance of HbA1c-related complications, and reduced insulin pump use [111]. CGM is also known to be cost effective in the management of patients with T2D not treated with prandial insulin [112].…”
Section: Introductionmentioning
confidence: 99%